Pengaruh Pembagian Kerja dan Pelatihan Kerja terhadap Kinerja Karyawan yang Dimediasi oleh Kepuasan Kerja pada Divisi Pemasaran PT. Asuransi Simas Jiwa Jakarta - Yochinia, Yedida (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study investigates the influence of work division and job training on employee performance, with job satisfaction as a mediating variable, focusing on the Marketing Division of PT. Asuransi Simas Jiwa Jakarta. The research is motivated by inconsistent sales performance in the division, which is suspected to be linked to unclear task allocation and irregular training programs. Employing a quantitative approach, the study surveyed all 35 employees using a saturated sampling technique. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS software. The findings reveal that job training has a significant and positive effect on job satisfaction (t = 9.556; p < 0.001), indicating the importance of well-structured training programs in enhancing employees’ confidence and adaptability. However, work division shows a positive but insignificant relationship with job satisfaction (t = 0.812; p = 0.417). Surprisingly, job satisfaction does not significantly influence employee performance (t = 1.638; p = 0.101), nor does it mediate the effects of work division and training on performance. Furthermore, neither work division nor training has a significant direct effect on performance. These findings suggest that improving employee performance requires more than just job structuring and training it demands a comprehensive human resource strategy, including performance incentives and active employee involvement in job design. Limitations of this study include a small sample size and focus on a single organization, which may restrict broader generalization.